Cell cycle dynamics of an M-phase-specific cytoplasmic factor in Xenopus laevis oocytes and eggs (The Rockefeller University Press, 1984)
We have examined the regulation of maturation-promoting factor (MPF) activity in the mitotic and meiotic cell cycles of Xenopus laevis eggs and oocytes. To this end, we developed a method for the small scale extraction of eggs and oocytes and measured MPF activity in extracts by a dilution end point assay. We find that in oocytes, MPF activity appears before germinal vesicle breakdown and then disappears rapidly at the end of the first meiotic cycle. In the second meiotic cycle, MPF reappears before second metaphase, when maturation arrests. Thus, MPF cycling coincides with the abbreviated cycles of meiosis. When oocytes are induced to mature by low levels of injected MPF, cycloheximide does not prevent the appearance of MPF at high levels in the first cycle. This amplification indicates that an MPF precursor is present in the oocyte and activated by posttranslational means, triggered by the low level of injected MPF. Furthermore, MPF disappears approximately on time in such oocytes, indicating that the agent for MPF inactivation is also activated by posttranslational means. However, in the absence of protein synthesis, MPF never reappears in the second meiotic cycle. Upon fertilization or artificial activation of normal eggs, MPF disappears from the cytoplasm within 8 min. For a period thereafter, the inactivating agent remains able to destroy large amounts of MPF injected into the egg. It loses activity just as endogenous MPF appears at prophase of the first mitotic cycle. The repeated reciprocal cycling of MPF and the inactivating agent during cleavage stages is unaffected by colchicine and nocodazole and therefore does not require the effective completion of spindle formation, mitosis, or cytokinesis. However, MPF appearance is blocked by cycloheximide applied before mitosis; and MPF disappearance is blocked by cytostatic factor. In all these respects, MPF and the inactivating agent seem to be tightly linked to, and perhaps participate in, the cell cycle oscillator previously described for cleaving eggs of Xenopus laevis (Hara, K., P. Tydeman, and M. Kirschner, 1980, Proc. Natl. Acad. Sci. USA, 77:462- 466).